Corn Commodity Diversification Policy And Implementation Of A Circular Economy: Steps Towards Sustainable Agriculture In Bone Bolango District - Abdul Wahab Podungge, Abdul; Yulianty Adipu, Yulianty; Robby Hunawa, Robby; Muhammad Altaf Ainul Khafit; Nila Kusuma; Annisa Sabina Adrias (Agri Analytics Journal, 2024)
This research is motivated by the importance of conserving corn plants by implementing the concept of sustainable agriculture using organic fertilizer. Researchers emphasize that the formulation of the problem of corn commodity diversification is the right step in overcoming economic challenges, especially in the context of a very comprehensive circular economy, a circular economy can maximize added value from each stage of production. This process supports the circular economy concept which focuses on the efficient and sustainable use of natural resources. By harnessing the full potential of corn, from seeds to waste, the circular economy can create a more sustainable value circle. The aim of this research is to analyze and present the implementation of a circular economy in corn crops by: 1) organic fertilizer can replace chemical fertilizer subsidies; 2) corn milk products can prevent and reduce the prevalence of stunting; 3) Corn cob waste can be used by farmers to make briquettes which have sales value. The research method used is a mixed method approach or a combination of qualitative and quantitative methods through: 1) direct observation carried out for four months on corn production activities; 2) interviews with key informants; 3) looking at literature. The research results show that: 1) liquid organic fertilizer from banana peel waste is effectively implemented because it can reduce production costs and is able to provide soil nutrition; 2) providing nutrition in corn milk has a positive impact as protein helps form muscle tissue, improves cell performance, and strengthens the immune system so that it can reduce stunting rates; 3) utilization of corn cob waste into effective briquettes in providing long-term solutions to agricultural sustainability